The effect of branched chain amino acids on psychomotor performance during treadmill exercise of changing intensity simulating a soccer game - Wisnik, P.; Chmura, J.; Ziemba, A. W.; Mikulski, T.; Nazar, K. (Applied Physiology, Nutrition, and Metabolism, 2011)
The present study was designed to determine changes in the multiple-choice reaction time (MRT) during treadmill running simulating locomotor activity during a soccer game and to examine the effect of branched chain amino acids (BCAA) ingestion on psychomotor performance during the effort. Ten male soccer players were submitted to BCAA and placebo trials at 1-week intervals in a randomized order. BCAA (7 g) or placebo were given 1 h before exercise in a double blind manner. The running test consisted of two 45 min exercise bouts separated by a 15-min passive rest period and the whole test ended with 20-min active recovery. Running-walking speed changed from 0 to 6.4 m/s according to the time-motion analysis of soccer match. During the test, blood samples were taken for lactate, glucose, free fatty acid, and catecholamine determination. Following placebo treatment, MRT shortened from 320 ± 18 to 271 ± 11 ms (p < 0.001) during the first exercise bout then it increased during the resting break to 303 ± 138 ms (p < 0.05). During the second bout, MRT decreased to 280 ± 13 ms (p < 0.001). During active recovery, further shortening of MRT was noted. During BCAA trial, MRT was shorter than during placebo trial by ~10% (p < 0.05) before and during exercise. No significant differences were found between BCAA and placebo trials in biochemical indices. It is concluded that BCAA supplementation might be recommended in sport activities that change in intensity and require quick responses to external signals (e.g., soccer and other team games).